Differential expression of the three Alcanivorax borkumensis SK2 genes coding for the P450 cytochromes involved in the assimilation of hydrocarbons. Issue 6 (9th November 2017) - Sevilla, Emma; Yuste, Luis; Moreno, Renata; Rojo, Fernando
Summary: Alcanivorax borkumensis, a marine bacterium highly specialized in degrading linear and branched alkanes, plays a key ecological role in the removal of marine oil spills. It contains several alternative enzyme systems for terminal hydroxylation of alkanes, including three P450 cytochromes (P450‐1, P450‐2 and P450‐3). The present work shows cytochrome P450‐1 to be expressed from the promoter of the upstream gene fdx . Promoter Pfdx was more active when C8 ‐C18 n ‐alkanes or pristane were assimilated than when pyruvate was available. The product of ABO_0199 (named CypR) was identified as a transcriptional activator of Pfdx . The inactivation of cypR impaired growth on tetradecane, showing the importance of the fdx ‐P450‐1 and/or cypR genes. P450‐2 expression was low‐level and constitutive under all conditions tested, while that of P450‐3 from promoter P450‐3 was much higher when cells assimilated pristane than when n ‐alkanes or pyruvate were available. However, the inactivation of P450‐3 had no visible impact on pristane assimilation. Cyo terminal oxidase, a component of the electron transport chain, was found to stimulate promoter PP450‐3 activity, but it did not affect promoters Pfdx or PP450‐2 . A. borkumensis, therefore, appears to carefully coordinate the expression of its multiple hydrocarbon degradation genes using both specific and global regulatory systems.